Conflicting Role of Mycobacterium Species in Multiple Sclerosis - Cossu, Davide; Yokoyama, Kazumasa; Hattori, Nobutaka (Frontiers in Neurology, 2017)
Mycobacterium is a genus of aerobic and acid-fast bacteria, which include several pathogenic organisms that cause serious diseases in mammals. Previous studies have associated the immune response against mycobacteria with multiple sclerosis (MS), a chronic demyelinating disease of the central nervous system with unknown etiology. The role of mycobacteria in the pathological process has been controversial and often conflicting. We provide a detailed review of the mycobacteria that have been linked to MS over the last three decades, with a focus on Mycobacterium bovis Bacille Calmette Guérin (BCG) vaccine for human and oral exposure to Mycobacterium avium subsp. paratuberculosis. We will also discuss the exposure and genetic susceptibility to mycobacterial infection, the protective role of vaccination, as well as the possible mechanisms involved in initiating or worsening MS symptoms, with particular emphasis on the molecular mimicry between mycobacterial and human proteins. Finally, we will introduce topics such as heat shock proteins and recognition by innate immunity, and toll-like receptor signaling-mediated responses to mycobacterium exposure.